2019
DOI: 10.5935/1518-0557.20190016
|View full text |Cite
|
Sign up to set email alerts
|

Environmental toxins and the impact of other endocrine disrupting chemicals in women's reproductive health

Abstract: This review aimed to look into agents and mechanisms characterized as endocrine disrupting chemicals (EDCs). These agents are known to cause several harmful effects to the reproductive system of women and wildlife. There is a wide range of chemicals, developed for commercial use mainly in agriculture, which may cause endocrine disruption. Numerous studies show evidence of environmental contamination. However, no one is being held liable for the damages. The most important potentially harmful agents are identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 110 publications
(120 reference statements)
0
47
1
1
Order By: Relevance
“…As such, our data identify gestation as a critical period for adult metabolic perturbations, with increased sensitivity of male offspring to the toxic effects of gestational benzene exposure. In contrast, the protective sex-specific effects in adult females observed in our recent study may have a hormonal basis (Piazza and Urbanetz 2019); however, a causal relationship for these observations remains to be elucidated.…”
Section: Discussioncontrasting
confidence: 73%
“…As such, our data identify gestation as a critical period for adult metabolic perturbations, with increased sensitivity of male offspring to the toxic effects of gestational benzene exposure. In contrast, the protective sex-specific effects in adult females observed in our recent study may have a hormonal basis (Piazza and Urbanetz 2019); however, a causal relationship for these observations remains to be elucidated.…”
Section: Discussioncontrasting
confidence: 73%
“…Female reproductive health is drastically affected by environmental factors such as toxins, drugs, and endocrine disruptors. 44,45 As for glyphosate, a potential EDC, many studies have shown hazardous effects of exposure to this chemical on endocrine system, indicating that it has potential reproductive toxicity via altering the reproductive endocrine function. 7 Moreover, some studies have provided indications of endocrine-disrupting effects induced by GBH at more environmentally relevant doses.…”
Section: Discussionmentioning
confidence: 99%
“…The possible role of environmental risk factors [ 7 , 8 , 9 ] or occupational risk factors [ 10 ] was investigated by some authors, highlighting contexts and exposures likely to be associated with the onset of the disease. There are two areas of potential risk that play a prominent role: exposure to chemical agents (particularly chemicals with xeno-estrogenic molecular activity [ 11 ]) and night work (linked to the interference on hormonal balance) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%